2013
DOI: 10.1523/jneurosci.4418-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Modulation of Feedback Integration during Singing: Role of the Right Anterior Insula

Abstract: Somatosensation plays an important role in the motor control of vocal functions, yet its neural correlate and relation to vocal learning is not well understood. We used fMRI in 17 trained singers and 12 nonsingers to study the effects of vocal-fold anesthesia on the vocal-motor singing network as a function of singing expertise. Tasks required participants to sing musical target intervals under normal conditions and after anesthesia. At the behavioral level, anesthesia altered pitch accuracy in both groups, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 80 publications
3
91
0
1
Order By: Relevance
“…Similarly, artificially pitch-shifted auditory feedback can lead to a modulation of the fundamental frequency of vocalizations in songbirds (Sober and Brainard, 2009), monkeys (Eliades and Wang, 2008) and humans (Burnett et al, 1998; Elman, 1981; Fairbanks, 1954). In this case, the subject’s extensive vocal training may have allowed him to rely on an internal model during singing, independent of any contradicting feedback (Kleber et al, 2013; Zarate and Zatorre, 2005; Zarate and Zatorre, 2008) and thus avoiding the resultant pitch change.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, artificially pitch-shifted auditory feedback can lead to a modulation of the fundamental frequency of vocalizations in songbirds (Sober and Brainard, 2009), monkeys (Eliades and Wang, 2008) and humans (Burnett et al, 1998; Elman, 1981; Fairbanks, 1954). In this case, the subject’s extensive vocal training may have allowed him to rely on an internal model during singing, independent of any contradicting feedback (Kleber et al, 2013; Zarate and Zatorre, 2005; Zarate and Zatorre, 2008) and thus avoiding the resultant pitch change.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a functional magnetic resonance imaging (fMRI) singing study demonstrated that both vocal students (enrolled in a performance program) and professional opera singers recruited more activity within S1 and somatosensory association cortex than amateur singers, and moreover, the amount of singing practice positively correlated with the activity in these regions (Kleber et al, 2010). In a more recent fMRI study, Kleber et al (2013) effectively reduced the amount of somatosensory feedback available by applying a topical anesthetic to the vocal folds just prior to singing in the MR scanner. The investigators determined that under vocal-fold anesthesia, singers displayed reduced activity in the right anterior insula than non-musicians, who had enhanced insular activity with anesthesia.…”
Section: Training Effects On the Sensory-motor Control Of Singingmentioning
confidence: 99%
“…Areas within the basal 100 ganglia (putamen) were more active for experts than for non-experts (J. M. Zarate and 101 Zatorre 2008), while the aINS was less active for experts than for non-experts 102 (Boris Kleber et al 2013). However, the network of areas recruited is extremely stable 103 throughout the singing literature and even shows some degree of overlap with the areas 104 recruited for speaking in both auditory and motor regions (Hickok et al 2003;Ozdemir, 105 Norton, and Schlaug 2006).…”
mentioning
confidence: 99%
“…However, 466 if subvocal humming was responsible for the larynx activation observed during cello 467 playing, it seems likely that other vocalization specific areas would also be recruited, from the body to support bi-manual coordination in piano playing (Parsons et al 2005) 480 and to coordinate the vocal musculature during singing (B. Kleber et al 2007) together 481 with other interoceptive inputs (Boris Kleber et al 2013). In our study, we found that 482 activity in the aINS and ACC was directly overlapping during cello playing and singing.…”
mentioning
confidence: 99%